2012
DOI: 10.1111/bdi.12011
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in bipolar disorder versus schizophrenia: comparability in mental state decoding deficits

Abstract: Mental state decoding difficulties are significant in BD. An important direction for further research will be to establish to what extent these deficits affect social and occupational functioning as a potential target for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
3
37
2
6
Order By: Relevance
“…Using a one-way ANCOVA, in which age and gender were entered as covariates, to compare Eyes Test scores between diagnostic categories ('Schizophrenia/Schizoaffective' versus 'Other Psychosis'), the 'SZ/SZA' group obtained significantly lower scores than the 'Other Psychosis' group on the Eyes Test (SZ/SZA: M = 19.79, S.D. = 6.51; Other Psychosis: M = 22.57, SD = 5.86; F = 10.484, p b p = 0.001), in keeping with previous studies (Donohoe et al, 2012;Guastella et al, 2013).…”
supporting
confidence: 89%
“…Using a one-way ANCOVA, in which age and gender were entered as covariates, to compare Eyes Test scores between diagnostic categories ('Schizophrenia/Schizoaffective' versus 'Other Psychosis'), the 'SZ/SZA' group obtained significantly lower scores than the 'Other Psychosis' group on the Eyes Test (SZ/SZA: M = 19.79, S.D. = 6.51; Other Psychosis: M = 22.57, SD = 5.86; F = 10.484, p b p = 0.001), in keeping with previous studies (Donohoe et al, 2012;Guastella et al, 2013).…”
supporting
confidence: 89%
“…From our PubMed search of more recent studies not included in the meta-analyses, a total of 16 of the 20 studies that examined adults with chronic schizophrenia either did not report on sex differences or controlled for sex in their FEP analyses [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] , with one study including an all-male sample [68] . Of the remaining four studies, three studies did not find sex differences on an FEP identification task [69][70][71] . By contrast, Erol et al [72] found sex differences in FEP: Chronically ill women with schizophrenia performed equivalently to men and women without schizophrenia on both identification and discrimination FEP tasks, while men with schizophrenia performed worse on both tasks.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 92%
“…There are several studies suggesting an impaired emotion recognition (Brotman et al 2008 ;Bozikas et al 2006 ;Lennox et al 2004 ;Getz et al 2003 ;Lembke and Ketter 2002 ;Loughland et al 2002 ;Yurgelun-Todd et al 2000 ;Addington and Addington 1998 ;Rubinow and Post 1992 ;Donohoe et al 2012 ;Derntl et al 2009 ;Lahera et al 2012 ;Martino et al 2011b ), but also several others report the opposite (Vaskinn et al 2007 ;Malhi et al 2007b ;Kucharska-Pietura and David 2003 ;Bellack et al 1996 ;Montag et al 2010 ;Olley et al 2005 ;Shamay-Tsoory et al 2009 ;Robinson et al 2008 ;Surguladze et al 2010 ). Negative fi ndings are reported especially after controlling for medication and other confounding variables (Martino et al 2011b ).…”
Section: Emotion Processingmentioning
confidence: 97%
“…Most studies report the presence of a defi cit concerning ToM and social cognition during all phases of BD (Cusi et al 2010 ;Adida et al 2011 ;Lahera et al 2008 ;Wolf et al 2010 ;Bora et al 2005 ;Donohoe et al 2012 ;Cusi et al 2012 ;Martino et al 2011b ;Inoue et al 2004 ;Scott et al 2000 ). Only a minority of studies is negative (Barrera et al 2012 ;Sarfati and Hardy-Bayle 1999 ).…”
Section: Tommentioning
confidence: 99%
See 1 more Smart Citation